The Effect of Reciting the Holy Qur’an to the Speaking Ability and Spirituality Level of Stroke Patient with Motor Aphasia - Slamet Purnomo; Ikhlas Muhammad Jenie (Jurnal Keperawatan Padjadjaran, 2020)
Reading therapy is a stimulation effort to improve language function of a patient with motor aphasia. This study aim was to examine the effect of reading therapy using holy Qur’an to the speaking ability and spirituality level of stroke patient with aphasia. This experimental study used nonequivalent control group design with 20 persons as sample, divided to 10 persons as the intervention group and 10 persons in the control group used purposive sampling technique. Measurement of the speaking ability used Frenchay Aphasia Screening Test (FAST) questionnaire and spirituality level used Functional Assessment of Chronic Illness Therapy (FACIT) Sp 12 questionnaire. The Result was significant improvement of speaking ability in the intervention group with mean difference was mean±SD (1,60±1,075). Post-experimental difference test showed the difference of improvement of speaking ability between two groups, P=0,034. The spirituality level also significantly improved in the intervention group with mean difference was mean±SD (6,80±3,190). Post experimental difference test showed the improvement of spirituality level in both groups with P=0,005. This therapy can be used as a rehabilitation training activity independently at home to improve the speaking ability also as part of spiritual activity.